The effectiveness of the argument-driven inquiry model based on the toulmin argumentation pattern on the argumentative writing skills of eleventh grade senior high school students - Fitri, Rahayu; Yulianti DN, Upit (Cendikia : Media Jurnal Ilmiah Pendidikan, 2025)
This study was motivated by the low ability of students to write argumentative texts that are logical, systematic, and evidence-based. The research aimed to examine the effectiveness of the Argument-Driven Inquiry (ADI) model based on the Toulmin Argumentation Pattern (TAP) in improving the argumentative writing skills of eleventh-grade students at SMA Negeri 3 Padang. The study employed a pre-experimental method with a one-group pretest–posttest design. The sample consisted of 37 students selected through simple random sampling. Data were collected using a performance test of argumentative writing and analyzed using normality testing, homogeneity testing, paired sample t-test, and N-Gain calculations. The results showed a significant increase in students’ argumentative writing skills after the implementation of the TAP-based ADI model, with the average score increasing from 59.60 (pretest) to 72.32 (posttest). The paired sample t-test produced a t-value of –18.714 with Sig. (2-tailed) = 0.000 < 0.05, while the N-Gain value of 0.31 fell into the medium category. These findings indicate that the TAP-based ADI model is effective in enhancing the argumentative writing skills of eleventh-grade students at SMA Negeri 3 Padang.